2017
DOI: 10.1177/0092055x17725131
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in Unfamiliar Terrain: Empowering Student and Teacher Learning through a Photography Assignment

Abstract: This article addresses a challenge for sociologists who teach at institutions located in unfamiliar cultural contexts through a photo elicitation project to develop students’ sociological imaginations while teaching the instructor about students’ social contexts. In introductory courses, we must present sociology as a field of study that is relevant for students’ lives and teach students to connect their experiences with sociological perspectives. For instructors unfamiliar with the social context shaping thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…These learning goals included encouraging the internalization of course material (DeJean, 2008) and enriching the connections among various aspects of a course (Patrick & Patrick, 2010). More commonly, instructors indicated that these assignments encouraged students to demonstrate their skills (e.g., visual methods, critical thinking) and knowledge of course material (e.g., visual methods, critical thinking) (Eisen, 2012;Grauerholz & Settembrino, 2016;Mount, 2018;Reid, 2016;Sargent & Corse, 2013;Whitley, 2013). Marquez-Zenkov and Harmon (2007, p. 24), however, focused their analysis of "student's images and writings" to explore students' literacy habits so that they could "adjust [their] pedagogy to meet their [students'] needs."…”
Section: Pedagogy Using Photographymentioning
confidence: 99%
See 1 more Smart Citation
“…These learning goals included encouraging the internalization of course material (DeJean, 2008) and enriching the connections among various aspects of a course (Patrick & Patrick, 2010). More commonly, instructors indicated that these assignments encouraged students to demonstrate their skills (e.g., visual methods, critical thinking) and knowledge of course material (e.g., visual methods, critical thinking) (Eisen, 2012;Grauerholz & Settembrino, 2016;Mount, 2018;Reid, 2016;Sargent & Corse, 2013;Whitley, 2013). Marquez-Zenkov and Harmon (2007, p. 24), however, focused their analysis of "student's images and writings" to explore students' literacy habits so that they could "adjust [their] pedagogy to meet their [students'] needs."…”
Section: Pedagogy Using Photographymentioning
confidence: 99%
“…Students indicate that photography-based assignments helped them to learn course concepts (Whitley, 2013) and make connections between course material and real life (Bragg & Nicol, 2011;Eisen, 2012;Grauerholz & Settembrino, 2016;Mount, 2018;Sargent & Corse, 2013;Whitley, 2013). But it remains unknown as to what course concepts they are learning or what specific connections they are making between coursework and real life.…”
Section: Pedagogy Using Photographymentioning
confidence: 99%
“…Scholars who have demonstrated the efficacy of using media to teach about gender and sexuality tend to draw on extant media, such as magazines (Curry and Clarke 1983), blogs (Noy 2014), and mainstream media, broadly (Moloney and Peleham 2014). Comparatively, fewer instructors have written about students collecting their own media to tell these gendered and sexual stories (see Mount 2018). Although not specifically discussing teaching gender or sexualities, Sparkman and Clary (2018) recently published assignment guidelines in the ASA's Teaching Resources and Innovations Library for Sociology for incorporating oral history into sociological courses, directly invoking storytelling as a highly effective assignment type.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…By far the most popular classroom exercise that utilizes visual material is the analysis of magazine advertisements to understand gender stereotypes (Curry and Clarke 1983). 6 But a growing number of courses are incorporating photography into classroom assignments, as well (Eisen 2012; Grauerholz and Settembrino 2016; Mount 2018; Sargent and Corse 2013; Whitley 2013). Most of these photography assignments have taken place in large survey courses, though Eisen (2012) and Sargent and Corse (2013) suggest ways that their assignments may be modified for advanced seminars.…”
Section: The Stories We Tellmentioning
confidence: 99%
“…Assessments of the above assignments suggest high student enthusiasm, appreciation for the creative nature of the assignment, and better understanding of sociological concepts and their application to the real world (Eisen 2012; Mount 2018; Sargent and Corse 2013; Whitley 2013). One of the drawbacks of photography, however, is that the ethics of photographing other people can be murky.…”
Section: The Stories We Tellmentioning
confidence: 99%